Design of Internal Model Control Based on an Optimal Control for a Servo System - Hiromitsu Ogawa; Ryo Tanaka; Takahiro Murakami; Yoshihisa Ishida (Journal of Control Science and Engineering)
This paper describes a design of internal model control based on an optimal control for a servo system. The control system has the feedback based on the proposed disturbance compensator in the disturbance response. The compensator is designed to become the denominator of the transfer function without a dead time in the disturbance responses. The disturbance response of the proposed method is faster than that of the previous method.